Éthos em rede: dinâmicas, apropriações e implicações éticas do éthos conectado no Facebook - Pereira, Marília Duque Estrada Soares (2016)
This work demontrates the performative and discursive scenes on Facebook. Considering the way Facebook interferes on both structures, this dissertation aims to explore the nature and dynamics of a Networked Éthos, which is mobilized and shared by social actors in order to shape the identity they wish to be recognized for in this social network. We argue that the éthos itself becomes a consumer good for others, working as a shared reputation indicator for those who maneuver it. Considering that consumption implies in a dispute of social capital, we observed the actor's behavior and interactions and its ethical implications while defining itself as a character. Due to the relevant role Facebook plays as a mediator and coactor on this communication system, we adopted a viewpoint that explores how the dispositive impacts over actors' performances, éthos apropriations and relational networks updates. Considering how Facebook itself appropriates the actors' éthos to encourage new engagements and to create profiles for target advertising practices, we were able to transform the observation results into an éthos typology that explains how the networked éthos operates on Facebook. In our conclusion, we also manage to conduct an ethical reflection of how this social network violates individual privacy and free will. Thus, we found out that the consumption of others reputation is not only an alternative for identity performance. More than that, it works to rescue actors from silence, giving them a way to be visible, to belong and to be loved.